Pemanfaatan Google My Business Untuk Meningkatkan Perekonomian Masyarakat Pada BUMDes Sumber Rejeki Desa Karangkemojing Kecamatan Gumelar - Nur Amalia Solikhah; Joko Dwi Mulyanto; Corie Mei Hellyana (BADAN PENERBIT STIEPARI PRESS, 2024)
The community service activity, focusing on the utilization of Google My Business to enhance the economy of BUMDes Sumber Rejeki in Karangkemojing Village, aims to improve the skills of local SME owners in introducing their businesses to a broader market. The training content is designed to enable the community to reach a wider audience, with the expectation of boosting the village's income. The goal is for participants to effectively utilize Google My Business as a promotional tool for the village to external audiences, emphasizing appealing designs and quality content. The execution method involves community service at Bina Sarana Informatika University, collaborating with the managers of BUMDes Karangkemojing Village. The training covers content creation and product promotion using Google My Business, accompanied by monitoring and evaluation stages. Solutions offered include learning how to create engaging content and effective promotion management. The anticipated outcomes encompass press releases in online and electronic media, along with an increase in the income of BUMDes managers who have been equipped with knowledge and technology. This, in turn, is expected to enhance the well-being of the local community in Karangkemojing Village.